Enhancing Students' Vocabularies Through Crossword Games for Students at SDI Tebuireng Abdul Wahid Hasyim - Hidayat, Dadan (Politeknik Negeri Bengkalis, 2023)
This quantitative research aimed to investigate of enhancing students' vocabulary through the implementation of crossword games in an experimental study conducted at SDI Tebuireng Abdul Wahid Hasyim. The research design employed is experimental, utilizing a pre-test and post-test control group design to assess the impact of crossword games on vocabulary enhancement. The study involves 21 students, divided into two groups: the treatment group, which received weekly crossword game sessions, and the control group, which did not undergo the intervention. The results indicate a noticeable improvement in vocabulary proficiency for the treatment group as evidenced by the post-test outcomes. This research contributes valuable insights into the potential of crossword games as an effective tool for fostering vocabulary development among students.